Developmental exposure to chlordecone induces transgenerational effects in somatic prostate tissue which are associated with epigenetic histone trimethylation changes. (July 2021) - Legoff, Louis; D'Cruz, Shereen Cynthia; Lebosq, Morgane; Gely-Pernot, Aurore; Bouchekhchoukha, Katia; Monfort, Christine; Kernanec, Pierre-Yves; Tevosian, Sergei; Multigner, Luc; Smagulova, Fatima
Highlights: Chlordecone exposure is associated with increased prostate cancer risk. Chlordecone increases prostatic epithelial neoplasia in F1 and F3 mice. In exposed mice, we observed alterations in histone H3K4me3. Hoxa genes are affected both in the prostate and in sperm of F1 and F3 generations. Abstract: Background: Chlordecone (CD), also known as Kepone, is an organochlorine insecticide that has been used in banana crops in the French West Indies. Due to long-term contamination of soils and water, the population is still exposed to CD. Exposure to CD in adulthood is associated with an increased risk of prostate cancer (PCa). Objectives: We examined the transgenerational effects of CD on murine prostate tissue. Methods: We exposed pregnant Swiss mice to CD. The prostates from directly exposed (F1) and non-exposed (F3) male progeny were analyzed. We used immunofluorescence, RNA-seq and ChIP-seq techniques for the comprehensive analyses of chromatin states in prostate. Results: We observed an increased prostatic intraepithelial neoplasia phenotype (PIN) in both F1 and F3 generations. Transcriptomic analysis in CD-derived F1 and F3 prostate using RNA-seq revealed that 970 genes in F1 and 218 in F3 genes were differentially expressed. The differentially expressed genes in both datasets could be clustered accordingly to common biological processes, "cell differentiation", "developmental process", "regulating of signaling", suggesting that in both generations similar processes were perturbed. We detected that in both datasets several Hox genes were upregulated; in F1, the expression was detected mainly in Hoxb and Hoxd, and in F3, in Hoxa family genes. Using a larger number of biological replicates and RT-qPCR we showed that genes implicated in testosterone synthesis ( Akr1b3, Cyp11a1, Cyp17a1, Srd5a1 ) were dramatically upregulated in PIN samples; Cyp19a1, converting testosterone to estradiol was elevated as well. We found a dramatic increase in Esr2 expression both in F1 and F3 prostates containing PIN. The PIN-containing samples have a strong increase in expression of self-renewal-related genes ( Nanog, Tbx3, Sox2, Sox3, Rb1 ). We observed changes in liver, F1 CD-exposed males have an increased expression of genes related to DNA repair, matrix collagen and inflammation related pathways in F1 but not in F3 adult CD-derived liver. The changes in RNA transcription were associated with epigenetic changes. Specifically, we found a global increase in H3K4 trimethylation (H3K4me3) and a decrease in H3K27 trimethylation (H3K27me3) in prostate of F1 mice. ChIP-seq analysis showed that 129 regions in F1 and 240 in F3 acquired altered H3K4me3 occupancy in CD-derived prostate, including highest increase at several promoters of Hoxa family genes in both datasets. The alteration in H3K4me3 in both generations overlap 73 genes including genes involved in proliferation regulation, Tbx2, Stat3, Stat5a, Pou2f3 and homeobox genes Hoxa13, Hoxa9. Conclusions: Our data suggest that developmental exposure to CD leads to epigenetic changes in prostate tissue. The PIN containing samples showed evidence of implication in hormonal pathway and self-renewal gene expression that have the capacity to promote neoplasia in CD-exposed mice.